Prognostic Factors in Rheumatoid Arthritis - Aslı Gençay Can; Zafer Günendi (Archives of Rheumatology, 2008)
Rheumatoid arthritis is a chronic, systemic, inflammatory disease that causes articular and extraarticular symptoms and affects quality of life. The clinical course of rheumatoid arthritis is variable. While a small percentage of patients with rheumatoid arthritis go into spontaneous remission, in approximately 20% of patients, chronic progressive disease may be developed despite treatment. Identification of prognostic factors may be predictive for assessing the prognosis and determining the patients who need early aggressive treatment. Either toxicity or high cost of treatment may also be prevented by avoiding over treatment in patients with rheumatoid arthritis who have good prognosis. High levels of acute phase reactants, seropositivity of rheumatoid factor and anti-CCP (anti-cyclic citrullinated peptides), HLA-DR4B1*O4 alleles, female gender, insidious disease onset, chronic synovitis with long duration, extraarticular manifestations, low grade education, high level of serum cartilage oligomeric matrix protein, presence of CD4(+), CD28(-) T cells, high level of macrophage migration inhibitory factor and poor functional capacity measurements are reported as poor prognostic factors in rheumatoid arthritis. (Rheumatism 2008; 23: 60-2)